Management of nutrients derived from natural fertilizers (manures) in the Polish agriculture – selected issues - Kopiński, Jerzy; Wach, Damian (Polish Journal of Agronomy, 2023)
The paper presents selected issues of managing nutrients from natural fertilizers used in Polish agriculture. The analysis covered changes in the livestock population and stocking density, the number and share of farms using natural fertilization, fertilized area and the level of consumption of particular nutrients from manures. Spatial analysis was carried out at the level of voivodeships (NUTS-2) and concerned the determination of the amount of nutrient from natural fertilizers in 2017–2020. The presented results indicate that the level of stocking density has the greatest impact on regional differences in the management of natural fertilizers. This diversity is also manifested in the share of farms using natural fertilization in individual voivodeships. Natural fertilizers in Poland, mainly manure, are used on 27% of UAA in good agricultural and environmental condition (UAA in GAEC). The share of four voivodeships, ie Podlaskie, Wielkopolskie, Łódzkie and Mazowieckie, covers 55% of the total area fertilized with manures in the country. In the years 2017–2020, the average consumption of solid manure in the country was44.3 million t, poultry manure 0.9 million t, liquid manure8.0 million m3 and slurry 14.6 million m3. The highest intensity of natural fertilization was found in the Podlaskie voivodeship, the average consumption was 11.4 t ha-1 of all agricultural land, while in Poland the average consumption was estimated at4.6 t ha-1 of UAA in GAEC. The highest doses per fertilized area were applied in the Podlaskie, Warmińsko-Mazurskie, Lubelskie, Lubuskie and Pomorskie voivodeships and it was directly related with the level of consumption of NPK from natural fertilizers in these voivodeships. In the analyzed period, the average doses of nitrogen, phosphorus and potassium applied to the manures’ fertilized area in Poland were 87 kg N ha-1, 29 kg P2O5 ha-1,113 kg K2O ha-1, respectively. The highest nutrient consumption in natural fertilizers was observed in Podlaskie voivodeship. Based on the analyses, it can be concluded that the Podlaskie voivodeship is a leader in the intensity of natural fertilizer management in Poland.